Pengembangan Desain Pembelajaran STEM dalam Kurikulum 2013 di Sekolah Dasar: Suatu Analisis dan Eksplorasi - Teti Haryati; Dindin Abdul Muiz Lidinillah; Karlimah Karlimah (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2020)
The design and learning of STEM in elementary schools are still not widely used in learning in elementary schools. STEM learning is relevant to the 2013 curriculum, like the current. Thematic learning. Thus, it is necessary to develop a STEM learning design, using development based research, namely EDR (Educational Design Research). The goal is to produce STEM learning projects that have been designed in the form of lesson plans for fifth-grade elementary school students. The method used in this research is development based research, namely EDR (Educational Design Research) with data collection techniques including interviews, discussions, observations, document analysis or documentation studies, and questionnaires. The subjects in this study were fifth-grade elementary school students. This article presents the analysis and exploration results, which is the first stage in this research, covering initial orientation, literature study, field-based investigations, field visits, professional meetings, and networking. This study aims to confirm that STEM learning in the 2013 curriculum is very appropriate for supporting the fulfillment of 21st-century skills for elementary students. The products produced from the first stage are problem definition, long term goals, partial design requirements, and initial designs.Keywords: STEM Learning, 2013 Curriculum, 21st Century Skills====================================================================================================Penelitian ini bertujuan untuk mengembangkan desain pembelajaran STEM di Sekolah Dasar dengan menggunakan penelitian berbasis pengembangan yaitu EDR (Educational Design Research). Penelitian ini menghasilkan proyek pembelajaran STEM yang telah dirancang yaitu RPP (Rencana Pelaksanaan Pembelajaran) untuk siswa kelas V Sekolah Dasar. Artikel ini menyajikan hasil analisis dan eksplorasi yang merupakan tahap pertama dalam penelitian ini, meliputi orientasi awal, studi literatur, investigasi berbasis lapangan, kunjungan lapangan, pertemuan profesional, dan jejaring dilakukan melalui berbagai metode: wawancara, diskusi, observasi, dan analisis dokumen dengan strategi meliputi: strategi sintesis kebijakan, bidang potret, kumpulan persepsi, dan analisis SWOT. Hasil dari penelitian ini yaitu mengkonfirmasi bahwa pemeblajaran STEM dalam kurikulum 2013 sangat tepat diterapkan dalam mendukung terpenuhinya keterampilan abad 21 bagi siswa Sekolah Dasar. Produk yang dihasilkan dari tahap pertama adalah definisi masalah, tujuan jangka panjang, persyaratan desain parsial dan desain awal.Kata kunci: Pembelajaran STEM, Kurikulum 2013, Keterampilan Abad 21